Peran Guru Dalam Manajemen Pembelajaran Proyek Berbasis Kewirausahaan Di Tkit Baitul Izzah Kota Bengkulu - Haryono, Mimpira; Suwarni, Suwarni; Bendriyanti, Rita Prima (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to describe the role of teachers in managing entrepreneurship-based project learning at Baitul Izzah Kindergarten (TKIT) in Bengkulu City, including the strategies implemented, the challenges faced, and their impact on the development of children's creativity and entrepreneurial spirit. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that teachers implemented project learning management through the planning, implementation, and evaluation stages, taking into account success indicators, namely creativity, cooperation, independence, problem-solving, responsibility, and understanding of entrepreneurial concepts. The strategies implemented by teachers included dividing students into small groups, using simple media, intensive mentoring, and adjusting activity schedules to address challenges such as limited resources, time, and differences in children's abilities. The implementation of entrepreneurship-based project learning had a positive impact on the development of children's entrepreneurial skills, enhancing creativity, critical thinking, cooperation, independence, and responsibility. This study confirms that the active role of teachers is crucial to the success of project learning and the development of children's entrepreneurial spirit from an early age.